1994
DOI: 10.1111/j.1574-6941.1994.tb00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Bacillus subtilis by DNA bound on clay in non-sterile soil

Abstract: Chromosomal DNA from Bacillus subtilis and different forms of plasmid pHV14 (covalently closed circular (CCC), linear monomer (M), and linear multimer (LM)) were adsorbed and bound on the clay mineral montmorillonite. After extensive washing of the clay‐DNA complexes with DNA buffer (pH 7.5), approx. 25% of the chromosomal DNA, and approx. 30, 90, and 5%, respectively, of the CCC, M and LM form remained bound. Chromosomal and plasmid DNA bound on clay were capable of transforming competent cells, with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(42 citation statements)
references
References 22 publications
0
42
0
Order By: Relevance
“…The artificial transformation and electroporation assays used indicated that the plasmid DNA did not suffer irreversible damage from soil incubation. Gallori et al (1994) used natural transformation assays to investigate the stability of clay-adsorbed DNA in soil samples. They found that clay-bound plasmid and chromosomal DNA of B. subtilis transformed competent B. subtilis cells after 15 days incubation in soil.…”
Section: Dna In Bacterial Cell Lysatesmentioning
confidence: 99%
“…The artificial transformation and electroporation assays used indicated that the plasmid DNA did not suffer irreversible damage from soil incubation. Gallori et al (1994) used natural transformation assays to investigate the stability of clay-adsorbed DNA in soil samples. They found that clay-bound plasmid and chromosomal DNA of B. subtilis transformed competent B. subtilis cells after 15 days incubation in soil.…”
Section: Dna In Bacterial Cell Lysatesmentioning
confidence: 99%
“…It appears that the low pH in the stomach, and nucleases produced in the saliva and small intestine can inactivate and degrade most ingested plant DNA and proteins (Duggan et al, 2000). Sometimes, however, small DNA fragments when bound to soil minerals or proteins can be absorbed in the GIT (Gallori et al, 1994). This process could protect them from degradation (El-Sanhoty et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Binding of DNA to rather different surfaces such as chemically purified mineral grains of sand, clay, non-purified mineral materials as well as humic substances has been reported (Khanna and Stotzky, 1992;Romanowski et al, 1992;Recorbet et al, 1993;Gallori et al, 1994;Lorenz and Wackernagel, 1994;Crecchio and Stotzky, 1998;Demanèche et al, 2001a). In the study of Demanèche et al (2001a) plasmid DNA adsorbed on clay particles was found to be not completely degradable even at high nuclease concentrations.…”
Section: Natural Transformationmentioning
confidence: 95%